Chromosomal Evolution and Evolutionary Relationships of Lebiasina Species (Characiformes, Lebiasinidae) - Francisco de Menezes Cavalcante Sassi (International Journal of Molecular Sciences, 2019)
We present the first cytogenetic data for Lebiasina bimaculata and L. melanoguttata with the aim of (1) investigating evolutionary events within Lebiasina and their relationships with other Lebiasinidae genera and (2) checking the evolutionary relationships between Lebiasinidae and Ctenoluciidae. Both species have a diploid number 2n = 36 with similar karyotypes and microsatellite distribution patterns but present contrasting C-positive heterochromatin and CMA3+ banding patterns. The remarkable interstitial series of C-positive heterochromatin occurring in L. melanoguttata is absent in L. bimaculata. Accordingly, L. bimaculata shows the ribosomal DNA sites as the only GC-rich (CMA3+) regions, while L. melanoguttata shows evidence of a clear intercalated CMA3+ banding pattern. In addition, the multiple 5S and 18S rDNA sites in L. melanogutatta contrast with single sites present in L. bimaculata. Comparative genomic hybridization (CGH) experiments also revealed a high level of genomic differentiation between both species. A polymorphic state of a conspicuous C-positive, CMA3+, and (CGG)n band was found only to occur in L. bimaculata females, and its possible relationship with a nascent sex chromosome system is discussed. Whole chromosome painting (WCP) and CGH experiments indicate that the Lebiasina species examined and Boulengerella maculata share similar chromosomal sequences, thus supporting the relatedness between them and the evolutionary relationships between the Lebiasinidae and Ctenoluciidae families.